Pressure leaching of copper sulphide from nickel refining: Initial experiments for valorisation. (1st May 2021) - Sinisalo, Pia; Jafari, Shila; Lundström, Mari
Highlights: Medium-temperature pressure leaching of copper sulphides was investigated. Copper extraction was over 99% at 165 °C at low final acidity (20–26 g/L). Sulphate formation (depended on T and acidity) increased copper extraction. Iron hydrolysis removed iron from the solution to levels acceptable for EW. Leach residue could be further sold as a by-product to precious metals refinery. Abstract: Copper sulphide rich leach residue from nickel refining is a marketable product and may be treated by smelting. In looking for another refining technology for its valorisation, the raw material was characterised and suitability of medium-temperature sulphate-based pressure leaching was tested for this purpose. The raw material contained 58% copper carried in covellite and copper oxides. Using favourable conditions, about two hours was needed for the completion of leaching. Copper extraction increased to over 99% with increasing sulphide oxidation to sulphate (92.3–99.8%) at 165 °C, and at low final acidity (20–26 g/L). In these conditions, the extraction of residual nickel was at least 99% and acid consumption 220–230 kg/t solids. The extent of sulphate formation appeared to depend on temperature, acidity and agitation. Sulphur agglomeration and scale formation occurred at low acidity between 125 and 145 °C. Iron hydrolysis during leaching was shown to remove iron from the solution to levels acceptable for electrowinning. The noble metals appeared to remain in the residue. In addition, significant portions of the impurities were released into solution. The copper dissolved could be subjected to direct recovery and the leach residue could be sold as a by-product to a precious metals refinery.